A national study on the prevalence and factors associated with smoking amongst Malaysians aged 18 years and above - Gyanchand Rampal, Lekhraj Rampal; Lekhraj Rampal, Sanjay Rampal; Md. Zain, Azhar; Mohd Sidik, Sherina; Mohamad, T.; Rahmat, Ramlee; Ahmad, J. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
A cross-sectional study was conducted in Malaysia with the objectives of determining the prevalence of smoking in Malaysia, reasons for starting to smoke, age first started to smoke, duration of smoking and to determine the relationship between smoking and age, sex, race, education level, peer influence and parental smoking status. Methods: All residents aged 18 years and above from selected households were included in this study. A standardised pre-tested structured questionnaire was used in this study. Results: The results showed that the overall mean age of the 17, 246 respondents was 38.8 (95% CI= 38.5 - 39.2) years with a range of 18 - 100 years. The majority were Malays (55.5%) followed by Chinese (21.2%) and Indians (11.2%). The age, sex and ethnicity adjusted prevalence of ever and current smokers were 32.0% and 24.9% respectively. The prevalence of ever and current smokers for males was 59.3% and 47.2% respectively. For the females, the prevalence of ever and CUlTentsmokers was 4.8% and 2.7% respectively. The highest ethnicity adjusted prevalence of current smokers was in Malays (28.9%), followed by the Chinese (18.7%). The lowest prevalence was amongst the Indians (16.8%). The highest prevalence of current smokers was found in Kelantan (30.2%), Terengganu (29.7%), Pahang (28.7%) and Kedah (26.9%); the lowest prevalence was in Kuala Lumpur, Federal Teritory (20.4%). The overall mean initiation age of current smokers was 19.2 years (95% CI = 19.1, 19.4 years). The mean initiation age of male current smokers was significantly lower (18.9 years) compared to female current smokers (24.1 years). The mean duration of smoking amongst the current smokers was 18.6 years. Males smoked significantly more cigarettes than the females ( p < 0.00 I). D isc u ssio n : Multivariate logistic regression analysis showed that smoking was significantly associated with age, sex, ethnicity, educational level and peer and family influence.